Study of the functinal characteristics and of the boot use by military policeman and its influence in the performance in the activity of patrol - Ana Claudia Vieira Martins; Sebastião Iberes Lopes Melo (Universidade Federal de Santa Catarina, 2005)
This descriptive diagnosis study had the objective to evaluate the functional characteristics and the use of the boots worn by the police officers while they are on duty patrol walking on Florianópolis streets, as well as the influency of the boots in this activity. Selected by not-probabilistic sampling in a casual-systematic way, 234 police officers volunteered to take part in this study. The instrument used was a questionnaire assorted with clarity level of 0.93, validity of 0.85 and reliability of 0.95. According to the results, most police officers have only a pair of boots, which were worn on average 11 hours daily. To the boot usage was attributed the incidence of foot injuries such as callosity, chilblain, embedded nails and blisters. For these police officers the discomforts (overheating, pain and humidity on the feet as well as pain in the body) caused by the boot interfered in their work routine taking them to classified their shoes as inappropriate, following the criteria of comfort, safety and durability. Therefore, it was concluded that the boots seemed not to be the ideal shoes in terms of comfort and job performance, because they interfered in their daily routine, causing functional and structural adaptations in the human body during the performance of motor tasks. RESUMO Este estudo descritivo diagnóstico teve como objetivo avaliar as características funcionais e de uso do coturno utilizado pelos policiais militares que realizam a tarefa de locomoção a pé durante as rondas nas ruas de Florianópolis, bem como sua influência nesta atividade. Selecionados por amostragem não-probabilística, casualsistemática por voluntariado, participaram 234 policiais militares. O instrumento utilizado foi um questionário misto com índice de clareza de 0,93, validade de 0,85 e fidedignidade de 0,95. De acordo com os resultados, a maioria dos policiais possui apenas um par de coturnos, permanecendo em média 11 horas diárias com este calçado, atribuindo a este a incidência de lesões nos pés, dos quais destacam as calosidades, frieiras, unhas encravadas e bolhas. Para estes policiais, os desconfortos causados pelo coturno interferem em suas rotinas de trabalho, tais como superaquecimento, dores e umidade nos pés e dores no corpo, conduzindo-os a avaliá-los como sendo calçados ruins, segundo os critérios de conforto, segurança e durabilidade. Conclui-se, portanto que, o calçado utilizado pelos policiais militares parece não adequado, em termos de conforto, para a tarefa a ser desempenhada por eles, pois acaba interferindo na rotina diária, imprimindo adaptações funcionais e estruturais do corpo humano na realização de tarefas motoras.